Examining the Causes and Consequences of Context-Specific Differential DNA Methylation in Maize . Issue 4 (13th April 2015) - Li, Qing; Song, Jawon; West, Patrick T.; Zynda, Greg; Eichten, Steven R.; Vaughn, Matthew W.; Springer, Nathan M.
Abstract : Natural variation of DNA methylation in maize is evident among five diverse maize inbred lines. Abstract: DNA methylation is a stable modification of chromatin that can contribute to epigenetic variation through the regulation of genes or transposons. Profiling of DNA methylation in five maize ( Zea mays ) inbred lines found that while DNA methylation levels for more than 99% of the analyzed genomic regions are similar, there are still 5, 000 to 20, 000 context-specific differentially methylated regions (DMR s) between any two genotypes. The analysis of identical-by-state genomic regions that have limited genetic variation provided evidence that DMR s can occur without local sequence variation, but they are less common than in regions with genetic variation. Characterization of the sequence specificity of DMR s, location of DMR s relative to genes and transposons, and patterns of DNA methylation in regions flanking DMR s reveals a distinct subset of DMR s. Transcriptome profiling of the same tissue revealed that only approximately 20% of genes with qualitative (on-off) differences in gene expression are associated with DMR s, and there is little evidence for association of DMR s with genes that show quantitative differences in gene expression. We also identify a set of genes that may represent cryptic information that is silenced by DNA methylation in the reference B73 genome. Many of these genes exhibit natural variation in other genotypes, suggesting the potential for selection to act upon existing epigenetic natural variation. This study provides insights into the origin and influences of DMR s in a crop species with a complex genome organization.